Pelvic Floor Disorders - Rizvi, Raheela M. (IntechOpen, 2018)
Pelvic floor disorders, which include urinary and fecal incontinence and pelvic organ prolapse, are highly prevalent conditions in women. In the United States alone, this affects almost 25% of women. These disorders often affect women's daily life activities, their sexual function, their ability to exercise, and their social and psychological life. Pelvic floor disorders are usually diagnosed clinically, but in complicated cases, pelvic imaging and electromyographic studies may be required. This book attempts to discuss the pathophysiology of pelvic floor disorders, its treatment by the use of a new synthetic material, and treatment for recurrent POP. Although there are many books available on this topic, it includes some of the original research work and surgical innovation. We would like to acknowledge all the authors for their hard work in completing this book.